Biodiversity Conservation and Sustainable Livelihoods Diversification: Insights and Policy Implications for Rural Communities in South Africa - MNISI, Pearl Thobeka (International Journal of Environmental, Sustainability, and Social Science, 2023)
This paper aims to analyze the effects of biodiversity conservation on sustainable livelihood diversification of rural communities in South Africa. Global evidence demonstrated a nuanced connection between biodiversity conservation and sustainable livelihood diversification. Biodiversity conservation is flourishing, and its industry has grown to a point where it accounts for a big part of South Africa's Gross Domestic Product. However, it remains a concern that the poverty levels in rural communities continue to rise, and there is no improvement brought by biodiversity conservation towards sustainable livelihood diversification. This is a theoretical paper that adopted the qualitative research method. The data for the paper was compiled through a desktop study wherein newspapers, scholarly journal articles, and government documents related to the effects of biodiversity conservation on sustainable livelihood diversification of rural communities in South Africa. Therefore, Document analysis was appropriate and selected to analyze the data. The paper found that balancing biodiversity conservation and sustainable livelihood diversification remains challenging in South Africa. This makes it difficult for rural communities to have sustainable livelihood diversification. This paper concludes that biodiversity conservation needs to do more justice to ensuring sustainable livelihood diversification for rural communities in the country. Therefore, it recommends the government delegate candidates or departments to continuously monitor and ensure that nature reserves practicing biodiversity conservation give back to nearby rural communities. Biodiversity conservation policies and legislations in line with the development of rural communities should be reviewed, adjusted, and ensured that they have operated accordingly.